Sosialisasi Peningkatan Kesehatan Reproduksi pada Remaja Putri Desa Tanjung Anom Sebagai Upaya Pencegahan Stunting Sejak Dini - Huwaina Af'idah; Balqis Nurmauli Damanik; Bulkis Putri Nazira HSB; Widya Jerni Gulo; Muhammad Qori Humadi; Gerson Zalukhu; Andi Zalukhu (Jurnal Kabar Masyarakat, 2023)
Stunting is one of the problems experienced by toddlers due to disruption of nutritional intake since pregnancy, which can hinder children's development and have long-term negative effects. Women who are not physically healthy enough to marry are more likely to have children who are short for their age. The aim of this service activity is to determine the relationship between early marriage and stunting in children. The questionnaire was used as a pre-test and post-test, by determining the average number of respondents who understood the information before and after being socialized on the topic of early marriage and adolescent reproductive health. The results of service activities show that the knowledge of young women in Tanjung Anom Village increased by >50% after being given material presentations by the PKM team. The suggestion given is to increase cross-sector collaboration between decision makers, so as to reduce the risk of stunting cases in the future.